PRELIMINARY NOTE ON HAMKA’S FRAMEWORK OF TAFSIR - Ahmad Nabil Amir (Journal of Malay Islamic Studies, 2021)
The paper discusses Quranic methodology of interpretation as set forth by Hamka (1908-1981) in Tafsir al-Azhar. It analyses the comprehensive method he crafted and the dynamic approach he brought out in textual exegesis. The extensive discussion and exposition of creative legal thought and ruling, history, mysticism, moral, theology, religion and culture reflected his typical and profound ijtihad (independent reasoning) and philosophy as substantively employed in this work. The method employed in this study was descriptive and analytical. It looked into themes brought forth in Tafsir al-Azhar and deduce its understanding and ideas that the author tried to formulate and projected. The study concluded that Tafsir al-Azhar was crafted based on certain al-adabi al-ijtima‘i’s approach (cultural social). It was a highly authoritative and monumental work produced with convincing analysis and being a dominant and vital reference in the work of tafsir in the Malay-Indonesian archipelago. The Tafsir emphasized on rational approach in understanding Quranic text reflecting the profound impact and inspiration from Tafsir al-Manar, its principal reference, and was highly influential in the intellectual tradition and modern development of tafsir that flourished in the Malay-Indonesian archipelago.